Regulations Rights Intellectual Property Regarding Digital Works Created by Artificial Intelligence (AI) - Nabil Lamonsya, Muhamad; Maulana, Puja; Alisra Chivalry, Muhammad; Fadhel Abd Jalil, Moh; Cahya Lestari, Adinda; Aulia Fatahillah, Ikhwan (VARIA HUKUM, 2025)
This article examines the challenges of regulating intellectual property rights (IPR) in Indonesia for digital works produced by artificial intelligence (AI). Although Law No. 28 of 2014 on Copyright establishes the creator as the legal subject, works produced automatically by AI create ambiguity in copyright ownership. This uncertainty creates a legal loophole that could lead to disputes. This study employs a normative juridical approach to analyse the legal protection of AI works and finds that, absent specific regulations, these works lack adequate legal protection. Concrete steps are needed, either through revisions to laws or through the establishment of new rules, to accommodate the development of AI technology and provide legal certainty for the owners of works.